Al-Ghazali and Viktor Frankl on Meaning: A Hermeneutic-Comparative Model of Psycho-Spiritual Integration - Rof Rof Galih Samudra; Sholahuddin Al Ayubi; Suadi Sa'ad (Yayasan Azhar Amanaa Yogyakarta, 2026)
The phenomenon of the crisis of meaning and spiritual emptiness in modern society reflects a gap between the advancement of modern psychology, which tends to be secular, and the profound spiritual needs of human beings. While modern psychology emphasizes empirical and behavioral aspects, Islamic Sufism through the concepts of tazkiyatun nafs (purification of the soul) and ma‘rifatullah (knowledge of God) offers a transcendental path toward genuine meaning in life. This study aims to analyze the concept of meaning in life according to Al-Ghazali and Viktor Frankl, and to synthesize both perspectives in order to develop an integrative psycho-spiritual model addressing the modern human meaning crisis. Using a qualitative library research method and a hermeneutic-comparative approach, this study integrates classical Sufi texts with modern logotherapy theory. The findings reveal that Al-Ghazali views the meaning of life as theocentric and rooted in divine revelation, whereas Frankl’s perspective is existential and based on human experience. The integration of both produces a psycho-spiritual model that harmonizes psychological and spiritual dimensions, offering relevance for the development of Islamic-based psychotherapy and the rediscovery of meaning in contemporary human life.